Truncating titin mutations are associated with a mild and treatable form of dilated cardiomyopathy - Jansweijer, Joeri A.; Nieuwhof, Karin; Russo, Francesco; Hoorntje, Edgar T.; Jongbloed, Jan D.H.; Lekanne Deprez, Ronald H.; Postma, Alex V.; Bronk, Marieke; van Rijsingen, Ingrid A.W.; de Haij, Simone; Biagini, Elena; van Haelst, Paul L.; et al. (European journal of heart failure, 2017)
Aims Truncating titin mutations (tTTN) occur in 25% of dilated cardiomyopathy (DCM) cases, but the phenotype and severity of disease they cause have not yet been systematically studied. We studied whether tTTN variants are associated with a clinically distinguishable form of DCM. Methods and results We compared clinical data on DCM probands and relatives with a tTTN mutation (n = 45, n = 73), LMNA mutation (n = 28, n = 29), and probands who tested negative for both genes [idiopathic DCM (iDCM); n = 60]. Median follow‐up was at least 2.5 years in each group. TTN subjects presented with DCM at higher age than LMNA subjects (probands 47.9 vs. 40.4 years, P = 0.004; relatives 59.8 vs. 47.0 years, P = 0.01), less often developed LVEF <35% [probands hazard ratio (HR) 0.38, P = 0.002], had higher age of death (probands 70.4 vs. 59.4 years, P < 0.001; relatives 74.1 vs. 58.4 years, P = 0.008), and had better composite outcome (malignant ventricular arrhythmia, heart transplantation, or death; probands HR 0.09, P < 0.001; relatives HR 0.21, P = 0.02) than LMNA subjects and iDCM subjects (HR 0.36, P = 0.07). An LVEF increase of at least 10% occurred in 46.9% of TTN subjects after initiation of standard heart failure treatment, while this only occurred in 6.5% of LMNA subjects (P < 0.001) and 18.5% of iDCM subjects (P = 0.02). This was confirmed in families with co‐segregation, in which the 10% point LVEF increase occurred in 55.6% of subjects (P = 0.003 vs. LMNA, P = 0.079 vs. iDCM). Conclusions This study shows that tTTN‐associated DCM is less severe at presentation and more amenable to standard therapy than LMNA mutation‐induced DCM or iDCM.